Chitinase Enzyme-Producing Endophytic Bacterias From the Roots of the Plant Gembolo (Dioscorea bulbifera): Isolation, Characterization and its Potential as an Antifungal Agent - Yunita, Vivi Alfi; Natsir, Hasnah; Ahmad, Ahyar; Baharuddin, Maswati (Universitas Jenderal Soedirman, 2024)
Chitinase is an enzyme of the chitinolytic group that has many roles in agriculture, especially as an antifungal, because chitin is one of the constituent components of the fungal cell wall. This study aimed to isolate and identify endophytic bacteria from gembolo (Dioscorea bulbifera) roots and to characterize the chitinase enzyme from these endophytic bacteria to be used as an antifungal. Isolation and identification of gembolo plant root endophytic bacteria using PCR method of 16S rRNA gene amplification and sequencing. Characterization of the chitinase enzyme produced includes determining of optimum pH, temperature, and substrate UV-Vis spectrophotometer. Antagonistic test of the chitinase enzyme and endophytic bacterial isolates (isolate K4) Fusarium oxysporum. The results showed that bacterial isolate K4 had with chitinolytic index of 2.45 mm. Electrophoresis results with PCR 16s rRNA gene; the length of the amplified fragment is the position of 1300 bp. By doing the BLAST process in GenBank, the bacterial isolate has 97.93% similarity with Enterobacter cloacae. Then, this endophytic bacteria is called Enterobacter cloacae K4-G. This bacterium produced chitinase enzyme reaching maximum chitinase activity at the 38 hours with an activity of 0.0312 U/mL. The chitinase characterization results of E. cloacae K4-G showed that the optimum conditions were reached at at pH 6, temperature 45 ᵒC, and 2.5% substrate with a chitinase activity value of 0.2467 U/mL. Chitinase enzyme and bacteria Enterobacter cloacae K4-G can inhibit the growth of the fungus Fusarium oxysporum. Therefore, Chitinase from Enterobacter cloacae K4-G can be used as an antifungal pathogen in plants.